2016
DOI: 10.1371/journal.pone.0167695
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Safe Food Handling among Consumers: A Systematic Review and Thematic Synthesis of Qualitative Research Studies

Abstract: Foodborne illness has a substantial health and economic burden on society, and most cases are believed to be due to unsafe food handling practices at home. Several qualitative research studies have been conducted to investigate consumers’ perspectives, opinions, and experiences with safe food handling at home, and these studies provide insights into the underlying barriers and facilitators affecting their safe food handling behaviours. We conducted a systematic review of previously published qualitative studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 55 publications
(55 reference statements)
3
59
0
Order By: Relevance
“…The organic food consumption per person shows an increasing trend but is still far below the world average level. Research shows that organic and green food buyers are mainly occasional consumers and inconsistency exists between stated willingness and revealed actual purchase [4,5]. Two main explanations are the lack of accessibility and the lack of knowledge of related labels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The organic food consumption per person shows an increasing trend but is still far below the world average level. Research shows that organic and green food buyers are mainly occasional consumers and inconsistency exists between stated willingness and revealed actual purchase [4,5]. Two main explanations are the lack of accessibility and the lack of knowledge of related labels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that it is well established that food safety training/education can be an effective strategy for improving knowledge and attitudes of food safety and may reduce the risk of food poisoning/ foodborne illness incidence (Zanin et al, 2017;Young et al, 2017) among consumers at the home (Young, et al, 2015;Young, and Waddell, 2016;Young et al, 2017;Evans and Redmond, 2014) and in different catering sectors (Seaman and Eves,2010) and retailing industry (Thaivalappil et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Methodologically, many of consumer food safety related studies are qualitative in nature. For example, Young, and Waddell (2016) carried out a review study on the barriers and facilitators to safe food handling among consumers, they found that 37 unique qualitative studies which used interviews, documents analysis for data collection. Another two recent qualitative study was conducted by Murray et al (2017) and Sterniša et al (2018) using a telephone interview to assess the effectiveness of food safety interventions over time, and know and attitudes of consumers, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Given that these students are early in the process of developing habits (5), high school may be an ideal time to teach food safety education. Family and friends also may play a role in propagating unsafe practices (47), particularly because young adults report first learning about food safety from their mothers, followed by fathers, school, and television (13), and because social pressures (46) and other psychosocial factors (45) appear to drive changes in food safety behaviors. Although we did not address these social and psychosocial factors, the high school environment may represent an opportunity to avoid development of unsafe food handling habits, combat potential negative influences of family and peers, and establish new social norms for safe food handling behaviors.…”
Section: Discussionmentioning
confidence: 99%